2020
DOI: 10.1002/maco.202012136
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and electrochemical characterization of Ti‐based amorphous metallic glass with high strength

Abstract: Ti‐based amorphous metallic glasses have excellent mechanical, physical, and chemical properties, which is an important development direction and research hotspot of metal composite reinforcement. As a stable, simple, efficient, and large‐scale preparation technology of metallic powders, the gas atomization process provides an effective way of preparing amorphous metallic glasses. In this study, the controllable fabrication of a Ti‐based amorphous powder, with high efficiency, has been realized by using gas at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Ti-based alloys have the advantages of high specific strength and strong corrosion resistance and are widely used as engineering materials [ 1 , 2 , 3 ]. At the same time, it has been found that amorphous alloys have superior mechanical properties, ductility and corrosion resistance compared to crystalline alloys [ 4 , 5 , 6 , 7 ]. Therefore, in recent decades, people have shown more and more interest in Ti-based amorphous alloys, and a lot of scientific research has been carried out [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ti-based alloys have the advantages of high specific strength and strong corrosion resistance and are widely used as engineering materials [ 1 , 2 , 3 ]. At the same time, it has been found that amorphous alloys have superior mechanical properties, ductility and corrosion resistance compared to crystalline alloys [ 4 , 5 , 6 , 7 ]. Therefore, in recent decades, people have shown more and more interest in Ti-based amorphous alloys, and a lot of scientific research has been carried out [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%